HISTORY OF THE DEVELOPMENT OF HINDUISM (Bulletin of Innovative Research, 2026)
This article provides a comprehensive analysis of the formation and historical development of Hinduism based on a religious and civilizational approach. The author interprets Hinduism not only as a belief system, but also as a socio-cultural phenomenon formed as a result of centuries-old historical experience. The influence of the caste system on the stability of society, religious tolerance, ritual traditions and religious pluralism is also scientifically examined. The results of the study serve to understand the historical stability, flexibility and transformations of Hinduism in modern times.